Prediction of rain-induced cross polarization at millimeter wave bands in guinea - Camara, Mamadi Fara; Saad Osman, Bashir; Mohd. Isa, Farah Nadia; Abdulwaheed, Musa (IEEE Explore, 2014)
Microwave communication systems are planned to utilize orthogonal polarization. Two independent information channels of the same frequency band sent over a single link to make an optimum use of the frequency spectrum. However, above 10 GHz, the amount of rain aloft can severely degrade the performance of both satellite and terrestrial links, especially in tropical regions, at millimetre wave bands. This paper evaluates the differential attenuation and differential phase shift for the prediction of cross polarization discrimination using a 10-year rain data recorded in Conakry, Guinea. The drop size distribution (DSD) was computed using Marshall and Palmer (MP) model.